Navigating the enhancement landscape: Ethical issues in research on cognitive enhancers for healthy individuals. (15th January 2013) - Forlini, Cynthia; Hall, Wayne; Maxwell, Bruce; Outram, Simon M; Reiner, Peter B; Repantis, Dimitris; Schermer, Maartje; Racine, Eric
Abstract : Research into the efficacy and safety of cognitive enhancers for recreational or lifestyle use has not been done. Should society pay for studies that might improve the lives of already healthy people?